The Single-Knot Running Vesicourethral Anastomosis after Minimally Invasive Prostatectomy: Review of the Technique and Its Modifications, Tips, and Pitfalls - Simone Albisinni; Fouad Aoun; Alexandre Peltier; Roland van Velthoven (Prostate Cancer)
The vesicourethral anastomosis represents a step of major difficulty at the end of minimally invasive radical prostatectomy. Over 10 years ago, we have devised the single-knot running vesicourethral anastomosis, which has been widely adopted in urologic departments worldwide. Aim of the current paper is to review the technique, its adaptability in complex situations, its complications, and possible modifications, including the use of barbed sutures.